Caracterização de um alphabaculovírus infectivo para larvas de Spodoptera eridania (Cramer, 1782) (Lepidoptera: Noctuidae) e a evolução de um gene homólogo de condroitina liase em baculovírus - Rodrigues, Daniela Teixeira (2020)
The southern armyworm (Spodoptera eridania) is native to the American tropics and is considered a polyphagous pest of great economic importance in several crops of Brazil. In this work, a new alphabaculovirus isolated from S. eridania was characterized at structural, biological and molecular levels. The isolate belongs to the EMBRAPA-Soja virus colection (Londrina, PR) and received the name Spodoptera eridania nucleopolyhedrovirus CNPSo-165 (SperNPV-CNPSo-165). Transmission and scanning electron microscopy showed that the SperNPV-CNPSo-165 occlusion bodies have a polyhedral shape with multiple virions per nucleocapsid. The virus demonstrated lethality for the third instar of S. eridania and S. albula (Walker) larvae, but not for S. frugiperda (J.E. smith) at the tested concentrations. The SperNPV-CNPSo-165 genome has 137,373 bp, 151 ORFs, 4 repetitive regions and a G+C content of 42.8%. Phylogenetic analysis based on the 38 baculovirus core genes indicated that the new virus is closely related to the common ancestor of isolates from other species within the Spodoptera complex, including another isolate also from S. eridania (SperNPV-251). Surprisingly, SperNPV-CNPSo-165 has a single copy of the odv-e66 gene, a bacterial homologue of chondroitin lyase, while viruses closely related to SperNPV-CNPSo-165 have two copies. Therefore, the evolution of odv-e66 in the Baculoviridae family was investigated. Thirteen deletions, sixteen acquisitions and one duplication of odv-e66 were found among the genomes of the baculoviruses characterized until then. The analysis suggest that the SperNPV-CNPSo-165 genome appears to have suffered independent loss of one of the copies of the gene. Thus, studies related to the characterization and evolution of baculoviruses can provide important information for the development and improvement of biological control tools.